Future research needs on climate change and food and nutrition security: Summary of findings of the CCAFS Working Paper: A synthesis of the work of CCAFS and partners on climate change and food and nutrition security - Nicholson, Charles; Cramer, Laura K.; Thornton, Philip K. (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2021)
CCAFS and partners have undertaken numerous activities and produced a considerable number of outputs of various kinds with the overarching goal to “catalyse positive change towards climate-smart agriculture, food systems and landscapes, and thereby contribute to the SLOs [System-level outcomes] on poverty alleviation, food and nutritional security.” A recent synthesis of the work of CCAFS and partners on food and nutrition security (FNS) discusses the contributions in detail. The synthesis was developed based on written materials and consultations with the CCAFS Program Management Unit, the CCAFS Flagships’ staff and CCAFS Regional programs. This Info Note highlights the knowledge gaps identified through the synthesis and recommended future actions.